Three-Dimensional Printing for Preoperative Planning and Pedicle Screw Placement in Adult Spinal Deformity: A Systematic Review. Issue 6 (July 2021) - Lopez, Cesar D.; Boddapati, Venkat; Lee, Nathan J.; Dyrszka, Marc D.; Sardar, Zeeshan M.; Lehman, Ronald A.; Lenke, Lawrence G.
Study Design: Systematic review. Objectives: This current systematic review seeks to identify current applications and surgical outcomes for 3-dimensional printing (3DP) in the treatment of adult spinal deformity. Methods: A comprehensive search of publications was conducted through literature databases using relevant keywords. Inclusion criteria consisted of original studies, studies with patients with adult spinal deformities, and studies focusing on the feasibility and/or utility of 3DP technologies in the planning or treatment of scoliosis and other spinal deformities. Exclusion criteria included studies with patients without adult spinal deformity, animal subjects, pediatric patients, reviews, and editorials. Results: Studies evaluating the effect of 3DP drill guide templates found higher screw placement accuracy in the 3DP cohort (96.9%), compared with non-3DP cohorts (81.5%, P < .001). Operative duration was significant decreased in 3DP cases (378 patients, 258 minutes) relative to non-3DP cases (301 patients, 272 minutes, P < .05). The average deformity correction rate was 72.5% in 3DP cases (245 patients). There was no significant difference in perioperative blood loss between 3DP (924.6 mL, 252 patients) and non-3DP cases (935.6 mL, 177 patients, P = .058). Conclusions: Three-dimensional printing is currently used for presurgical planning, patient and trainee communication and education, pre- and intraoperative guides, and screw drill guides in the treatment of scoliosis and other adult spinal deformities. In adult spinal deformity, the usage of 3DP guides is associated with increased screw accuracy and favorable deformity correction outcomes; however, average costs and production lead time are highly variable between studies.